Supramolecular Diiodine-Bromostannate(IV) Complexes: Narrow Bandgap Semiconductors - Nikita A. Korobeynikov; Andrey N. Usoltsev; Pavel A. Abramov; Maxim N. Sokolov; Sergey A. Adonin (Molecules, 2022)
Three supramolecular bromostannates(IV) with “trapped” diiodine molecules, Cat2{[SnBr6](I2)} (Cat = Me4N+ (1), 1-MePy+ (2) and 4-MePyH (3)), were synthesized. In all cases, I2 linkers are connected with bromide ligands via halogen···halogen non-covalent interactions. Articles 1–3 were studied using Raman spectroscopy, thermogravimetric analysis, and diffuse reflectance spectroscopy. The latter indicates that 1–3 are narrow band gap semiconductors.